Fungal evasion of Drosophila immunity involves blocking the cathepsin-mediated cleavage maturation of the danger-sensing protease - Guirong Tang; Shuangxiu Song; Junmei Shang; Yujuan Luo; Shiqin Li; Dongxiang Wei; Chengshu Wang (Proceedings of the National Academy of Sciences, 2025)
Entomopathogenic fungi play a critical role in regulating insect populations, and representative species from the Metarhizium and Beauveria genera have been developed as eco-friendly biocontrol agents for managing agricultural insect pests. Relative to the advances in understanding antifungal immune responses in Drosophila , knowledge of how fungi evade insect immune defenses remains limited. In this study, we report the identification and characterization of a virulence-required effector Fkp1 in Metarhizium robertsii . Library screening and protein pull-down analysis unveiled that Fkp1 targets the cathepsin protease CtsK1 to inhibit its cleavage maturation of the danger-sensing serine protease Persephone (Psh), thereby facilitating fungal evasion of the Drosophila immune defenses. The Fkp1 -like gene is also required in Beauveria bassiana for insect infection. Transgenic expression of Fkp1 in Drosophila suppressed hemolymph cysteine protease activity and down-regulated the expression of antifungal genes. Fkp1 can also mask the Psh cleavage site without interfering with its ability to bait fungal subtilisin proteases. Given the evident compensatory relationship, our data indicate that the protease cascade is more crucial than the molecular pattern pathway in defending flies against fungal infections. This work reveals that Metarhizium fungi have evolved distinct effectors to block the dual recognition pathways of flies for immune evasion and sheds lights on the effector mechanisms mediating microbe–animal interactions.